Proteomics Unravels Emodin Causes Liver Oxidative Damage Elicited by Mitochondrial Dysfunction - Zhang, Yinhuan; Yang, Xiaowei; Jia, Zhixin; Liu, Jie; Yan, Xiaoning; Dai, Yihang; Xiao, Hongbin (Frontiers in Pharmacology, 2020)
Emodin is one of the main active compounds in many Chinese traditional herbs. Due to its potential toxic effect on the liver, the possible injury mechanism needs to be explored. In the present study, we investigated liver injury mechanisms of emodin on rats by the technology of proteomics. Firstly, 4530 proteins were identified from the liver of rats treated with emodin by label free proteomics. Inside, 892 differential proteins were selected, presenting a downward trend. Bioinformatics analysis showed that proteins interfered with by emodin were mainly involved in oxidation-reduction biological processes and mitochondrial metabolic pathways, such as mitochondrial fatty acid β-oxidation, citric acid cycle, and oxidative phosphorylation, which were further confirmed by western blot. The decrease in maximal respiration, ATP production, spare respiratory capacity, and coupling efficiency and increase in proton leakage were detected by seahorse XFe 24 analyzer, which confirmed the damage of mitochondrial function. The down-regulated expressions in antioxidant proteins were verified by western blot and a significant increase of ROS levels were detected in emodin group, which showed that emodin disrupted redox homeostasis in livers. Molecular docking revealed that the main targets of emodin might be acadvl and complex IV. Generally, emodin could induce oxidative stress in livers by directly targeting acadvl/complex IV and inhibiting fatty acid β-oxidation, citric acid cycle, and oxidative phosphorylation taken place in mitochondria.